An IDS for DDoS Attacks in SDN using VGG-Based CNN Architecture - Muhammad, Mamdouh; Alshraa, Abdullah; German, Reinhard (The 31st International Conference on Software, Telecommunications and Computer Networks (SoftCOM 2023), 2023)
Keywords: Software Defined Networking; Denial-of-service attack; Deep Learning; Transfer learning; Feature extraction; Intrusion detection

Combined QoS Analysis of Smart Distribution Grids with Constraint Satisfaction Problem and Network Calculus - Alshraa, Abdullah; Vietz, Matthias; Hielscher, Kai-Steffen; Oest, Frauke; Lehnhoff, Sebastian; German, Reinhard (2023 IEEE International Conference on Communications, Control, and Computing Technologies for Smart Grids, SmartGridComm 2023 - Proceedings, 2023)
The expansion of renewable energies requires implementing Smart Grid Services (SGSs) in the distribution grid. Analytical verification of the SGSs' Quality of Service (QoS) requirements is crucial for reliable operation. This paper proposes a two-step approach: a constraint satisfaction problem (CSP) considers network infrastructure and resource allocations to find candidates' solutions. Then, the solutions are evaluated using Network Calculus (NC) to calculate delay bounds at the worst-case and compare them to the requirements. If necessary, alternative solutions are generated. The NC framework is adjustable and considers different service priorities by implementing scheduling policies such as strict priority, weighted fair queuing, weighted round robin, and deficit round robin. In the end, the best-performing parameters are derived for a sample network and the results manifest that the NC framework can be used to analyze random communication networks.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Network Calculus; Quality of Service; Smart Distribution Grid; Smart Grid Services

Cybersecurity strategies for smart grids: Leveraging agile IoT and IIoT integration - Alshraa, Abdullah; Muhammad, Mamdouh; German, Reinhard (IGI Global, 2024)
The incorporation of information and communication technologies (ICT) into power grids has brought a new generation in energy management, known as smart grids. This digital transformation has also raised new challenges to cybersecurity. This chapter presents the architecture and cybersecurity interplay within smart grids, highlights the need to secure critical infrastructure, and outlines the security requirements and the importance of availability, integrity, and confidentiality. Also, it discovers potential cyber-threats and vulnerabilities inherent in smart grids and analyzes historical incidents to provide insight into real-world implications. Moreover, the strategies for safeguarding smart grids components, such as supervisory control and data acquisition (SCADA) and industrial control systems (ICS), are discussed, alongside a unified framework to address privacy concerns. Finally, the chapter predicts future trends, identifies pioneering issues, and draws tracks for continuous research and development to strengthen smart grids' resilience against evolving threats.
CRIS-Team Scopus Importer:2024-08-16

Estimating the Influence of SDN Controller Intervention on Smart Grid Services - Alshraa, Abdullah; Maile, Lisa; Hielscher, Kai-Steffen; German, Reinhard (2023 IEEE Green Energy and Smart Systems Conference, IGESSC 2023, 2023)
The integration of Software Defined Networking (SDN) to manage Smart Grid Services (SGSs) has raised concerns about its impact on the end-to-end response times in the system. This paper investigates the Quality of Service (QoS) of SGSs in SDN environments using Constraint Satisfaction Problem (CSP) and Network Calculus (NC) techniques. Our studies show that the implementation of SDN contributes to an increase in end-to-end delay times and negatively affects the QoS of SGSs. These results provide insights for designing more efficient and reliable energy systems with SDN environments.
CRIS-Team Scopus Importer:2023-12-22
Keywords: Constraint Satisfaction Problem; Network Calculus; Quality of Service; Smart Grid Services; Software Defined Networking

Multipath TCP for Short Flows Supported by SDN in Heterogeneous Networks - Abumihsan, Ahmad; Awad, Abdalkarim; Jubran, Mohammad; Qaroush, Aziz; Tumar, Iyad; Alshraa, Abdullah (2023 8th International Conference on Computer and Communication Systems, ICCCS 2023, 2023)
Multipath TCP (MPTCP) offers better performance, throughput, and resilience in connection failure cases by dividing the flow into multiple subflows and submitting them over many paths. Generally, MPTCP has a perfect impact on long flows in terms of throughput once transferring data with big sizes. However, MPTCP may degrade the efficiency of short flows, which are sensitive to latency (e.g., web transfer applications). This work investigates the impact of MPTCP on short flows in homogeneous and heterogeneous networks and confirms that a bandwidth gap between paths is a critical factor influencing the performance of the short flows. Therefore, the work uses Software-Defined Networking (SDN) architecture to address the MPTCP problems and improves its performance for short flows. Our performance results show an improvement in MPTCP performance for short flows compared to the disjoint approach.
CRIS-Team Scopus Importer:2023-11-17
Keywords: heterogeneous networks; MPTCP; SDN; TCP

Security Principles in Smart and Agile Cybersecurity for IoT and IIoT Environments - Alshraa, Abdullah; Al Sardy, Loui; Dibaei Asl, Mahdi; German, Reinhard (Security Principles in Smart and Agile Cybersecurity for IoT and IIoT Environments, 2024)
As the integration of the internet of things (IoT) and industrial internet of things (IIoT) technologies continues to increase across various industries, ensuring strong cybersecurity measures becomes essential. In smart and agile cybersecurity for IoT and IIoT environments, foundational principles like risk management, security controls, governance, and a code of ethics are required. Risk management involves proactively identifying and mitigating potential threats, and ensuring the resilience of interconnected systems against cyber-attacks and vulnerabilities. Similarly, robust security controls, including encryption protocols and access management tools, provide essential layers of defense, safeguarding sensitive data and preventing unauthorized access. Furthermore, effective governance structures establish clear responsibility and guide policy implementation, enabling adherence to regulatory requirements and organizational objectives. Eventually, a strict code of ethics emphasizes the ethical imperatives basics in cybersecurity practices, enabling integrity, transparency, and respect for privacy rights. Through a comprehensive study of these topics, this chapter aims to provide readers with the necessary knowledge and strategies to steer the complexity of cybersecurity in IoT and IIoT environments efficiently, enabling resilience and adaptability against evolving threat

Survey of Cybersecurity in Smart Grids Protocols and Datasets - Muhammad, Mamdouh; Alshraa, Abdullah; German, Reinhard (Procedia Computer Science, 2024)
Smart grids are two-way communications grids that converge Information Technology (IT) and Operational Technology (OT) to transfer energy-related information between different industry components within the grid. Smart grids have changed the energy sector by increasing sustainability, efficiency and integrating renewable energy sources. However, smart grids are vulnerable to IT-related attacks because they rely on Information and Communication Technology (ICT). By surveying relevant papers and evaluating accessible statistics, this study explores cybersecurity in smart grids by examining current communication protocols and standards. We carefully compile various datasets with general information about four of the most smart grid-related datasets. Our study and conclusions address the key components of a smart grid and offer information that can help create cybersecurity plans specifically for smart grids. This research contributes to the discourse on smart grid security, which is important for preserving the stability of contemporary energy systems.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Cyber-Physical Systems; cybersecurity; Information Technology; IT/OT convergence; smart grids